Quantifying visual abstraction quality for stipple drawings - Spicker, Marc; Hahn, Franz; Lindemeier, Thomas; Saupe, Dietmar; Deussen, Oliver (My University, 2017)
We investigate how the perceived abstraction quality of stipple illustrations is related to the number of points used to create them. Since it is difficult to find objective functions that quantify the visual quality of such illustrations, we gather comparative data by a crowdsourcing user study and employ a paired comparison model to deduce absolute quality values. Based on this study we show that it is possible to predict the perceived quality of stippled representations based on the properties of an input image. Our results are related to Weber-Fechner's law from psychophysics and indicate a logarithmic relation between numbers of points and perceived abstraction quality. We give guidance for the number of stipple points that is typically enough to represent an input image well.
Keywords: Visual Abstraction, Quantitative Evaluation, User Study, Perception, Stippling, Non-Photorealistic Rendering; 004